QUALITY CONTROL OF MEDICAL AND PHARMACEUTICAL GOODS AND STANDARDIZATION - Otabek Kozimbek o’g’li, Shavkatov (Scientific Impulse, 2023)
One common source of misunderstanding in the medical device industry is the method the various national regulatory systems use to identify standards. This article explains the method, starting with standards from the International Organization for Standardization (ISO) adopted and recognized in various regulatory systems. ThearticleusesISO 13485:2016 andISO 9001:2015 asillustrations.